Alternator noise reduction based on claw-pole optimization. (September 2022) - Huang, Taiming; Li, Weiping; Yue, Wanhao; Ji, Nianzhou; Ou, Changjie; Wang, Xiaoshan; Guan, Chenglin
Highlights: Optimize the high-frequency aerodynamic noise during the high-speed operation of claw-pole alternator. The Latin hypercube sampling method is employed to optimize the structure of the claw-pole. Abstract: The high-frequency aerodynamic noise of claw-pole alternator presents a harsh sound in human subjective perception, which has an important impact on the car passengers' comfort. Therefore, experimental and optimization studies have been conducted to investigate the high-frequency aerodynamic noise during the high-speed operation of claw-pole alternator. In this study, a claw-pole alternator was first tested under no-load conditions. The experimental results revealed that the 6th, 9th, 12th, 18th, 30th and 36th orders are the main noise orders. Meanwhile, the dipole was the main noise source at a speed range of 8000–14, 000 rpm. Subsequently, a hybrid simulation method was applied to solve the acoustics field problem. The simulation and experimental results of the acoustics field characteristics satisfactorily agreed for all main orders of the aerodynamic noise at both speeds of 8000 and 12, 000 rpm. The minimum error for the 9th order was 0.35dBA at 8000 rpm, whereas the minimum error of the 8th order reached 0.51 dBA at a speed of 12, 000 rpm. Thus, the proposed simulation model could be considered a reliable approach. Additionally, the pressure amplitude distribution on the rotor surface for different orders was analyzed. The higher-pressure amplitudes at higher orders, such as the 30th and 36th orders, are mainly distributed at the claw-pole near the stator and root of the claw-pole, indicating that higher acoustics levels corresponding to the higher orders are mainly associated with the claw-pole. Finally, the claw-pole notching was parametrically modeled, and the eigenvalues of the radial, the notch inclination angle and the axial stretch length were optimized by using Latin hypercube sampling method. After notching, the air mass flow through the front and rear blades exhibited small changes, which slightly affected the cooling performance of the alternator. The claw-pole notching yielded the highest optimization, when the eigenvalues of radial, notch inclination angle and axial stretch length were 46.82 mm, 63.3° and 14.65 mm respectively.